Application level of lean construction techniques in reducing accidents in construction projects. Issue 3 (4th November 2019) - Enshassi, Adnan; Saleh, Nour; Mohamed, Sherif
Abstract : Purpose: This paper aims to investigate the application of lean construction (LC) techniques in reducing accidents in construction projects. Design/methodology/approach: A quantitative approach was used to collect the required data using a questionnaire survey and descriptive analysis was used to analyse the collected data. The LC techniques that were investigated in this paper are related to the tools of the last planner system (LPS), increased visualisation (IV), 5S, error-proofing, daily huddle meetings (DHMs), first-run studies (FRS), continuous improvement (Kaizen) and accident investigation (5Whys). Findings: The overall results indicated that LC techniques are poorly implemented in construction projects in the Gaza Strip. The top three LC tools used to reduce the causes of accidents in the Gaza construction projects were 5Whys, 5S and LPS, while the highest three LC techniques applied to reduce the causes of accidents that were applicable were cleaning the workplace and removing materials and machines that are not required; conducting accident investigation and root cause analysis programmes; and using safety signs and labels on site. Research limitations/implications: There is a lack of information and published studies regarding the links between LC and safety, especially in the Middle East. This paper is limited to the perceptions and geographical boundaries; therefore, it cannot be generalised. However, it could form the basis for useful comparison in the future. Triangulation research method could also be used in future research to minimise the bias and validate the conclusions. Practical implications: The findings of this paper will stress professionals and construction companies in Gaza to reconsider their behaviour towards using LC techniques. The findings of this paper will aid them to shift their attention and resources towards including LC techniques in their plans to reduce the causes of accidents on construction sites. Social implications: The findings of this paper will encourage professionals and construction companies in Gaza to reconsider their behaviour towards using LC techniques. The findings will also aid them to shift their attention and resources towards including LC techniques in their plans to reduce and/or avoid the causes of accidents on construction. Originality/value: Because of the lack of published works that are specific to the Middle East, the authors believe that the originality lies in the paper's serious attempt to explore the application level of the LC concept to safety in this part of the world. This paper contributes to a better understanding of the applicability of LC techniques in terms of accidents reduction. Findings from this paper provide a clear picture of the current status of using LC techniques to reduce accidents in the Gazan construction projects which drive them to investigate the main barriers and try to overcome them.